Bachelor Level Students Misconception in Chemistry Education - Ghimire, Paras Mani (Ganeshman Darpan, 2024)
This study aims to investigate the "Bachelor Level Students Misconception in Chemistry Education" I applied quantitative and qualitative research design (Quan-qual) with the use of descriptive using the data obtained from the set of conceptual questions. The sample consisted of 40 bachelor’s secondary major chemistry students in Mahendra Ratna Campus, Tahachal Kathmandu. I used in this study for identifying the misconception about chemistry were through the questionnaire. A set of 30 conceptual questions were given to the Bachelor’s second-year students. where the student had to give reasons to identify their source of knowledge, with their answers. Each item of the misconception test consisted of multiple-choice question. My research finding most of the students in chemistry has misconception which has affected the learning of students. This suggests the conclusion that there is some common misconception in chemistry among bachelor’s level students. The maximum number of students developed the falsified concept in organic chemistry portion which is followed by inorganic and physical chemistry. Most of the students’ source of misconception in science was found to be from their own intrinsic knowledge.